Different role of graphene for nonisothermal crystallization behavior of graphene filled poly(ether ether ketone) by different perparation methods. Issue 1 (20th February 2020) - Yu, Fei; Xiao, Linghan; Liu, Yu
Abstract: The nonisothermal crystallization investigation on different contents of graphene filled PEEK nanocomposites by ball milling and solution dispersed was performed on differential scanning calorimetry. Jeziorny and Mo's methods were selected to evaluate the result, so as to investigate the nonisothermal crystallization kinetics of pure PEEK and two kinds of PEEK/GE nanocomposites. Mo's method was demonstrated to be the most appropriate model to represent the crystallization behavior for neat PEEK and PEEK/GE nanocomposites under nonisothermal condition. The result showed that the absolute degree of crystallinity of both PEEK/GE nanocomposites decreased with increasing the content of graphene, but increased the nucleation activity for the nanocomposites. When the addition of graphene was 1 wt%, the dispersed method affected the crystallization mechanisms obviously, either promoting or hindering the polymer matrix crystallization. Overall, the method that filling graphene to PEEK matrix had influence on the nonisothermal crystallization process, hence affected the properties of nanocomposites. Abstract : In order to research the effect of ball milling and solution dispersed graphene on the PEEK crystallization process, the nonisothermal crystallization behavior for nanocomposites with different contents of graphene was investigated in this paper. As shown, the nucleation activity was increased with the addition of graphene to the PEEK matrix gradually. However, when the content of GE was 1.0 wt% in PEEK/GE② nanocomposites, the nucleation activity is the highest.